Epidemiological study on Buccal Health in the 12 years old population of Health Care Area VIII in Cienfuegos. - Yumaidi Colina Sánchez; Beatriz García Alpízar; Esther María Castillo Betancourt; Mikhail Benet Rodríguez; Raúl López Fernández; Manuel Rodríguez Rodríguez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2007)
Background: The 12 years-old children population is worldwide taken as a reference age to compare the buccal health condition of different countries, by means of various indicators that measure the presence of the main buccal diseases. The knowledge of these epidemiological profiles generates information to guide the services planning policies of the Primary Health Care. Objective: To characterize 12 years-old population's buccal health condition. Methods: Cross- sectional descriptive correlative study with a stratified probabilistic sample of 90 children starting from a universe conformed by the 269 adolescents that constitute the total of the 12 years old population of the Health Care Area VIII in Cienfuegos municipality. Pearson's chi-square and Mantel-Haenszel lineal tendency tests were used with the determination of the relative risk and reliance intervals of 95%. Results: The decay prevalence reached 54, 4%. The COP-D index was 2, 45 being the decayed component the major percentage with 4.6%. The periodontal disease was more frequent in boys than in girls, with 54, 9% and 30, 8% respectively. 80,9% of the segments is healthy. In those affected, the calculation prevailed in 11,7%. It was determined that faulty obturations, inheritance and faulty buccal hygiene were the most affecting risk factors for children with decays, while in the periodontal disease it was faulty buccal hygiene. Malocclusions presented a prevalence rate of 40%. Out of which, 55,6% required secondary level attention. Those with habits present a risk 2 times superior of making sick. The sick epidemiological category was present in 77,8% of the total. Conclusions: We emphasize the prevention need as core issue of the primary medical care in the world today; being the General-Integral Dentist a transforming agent that according to his/her formation is capable to assume the existent health problem and to modify it positively, acting from the earliest ages.